2020
DOI: 10.1177/1753193420916418
|View full text |Cite
|
Sign up to set email alerts
|

Distal radius fracture volar locking plate osteosynthesis using wide-awake local anaesthesia

Abstract: Surgical fixation of distal radius fractures under local anaesthesia with the patient wide awake allows an intraoperative testing of the fixation stability under active mobilization. We evaluated the feasibility and clinical results of this technique in 45 patients prospectively in two matched comparable groups: wide-awake local anaesthesia no tourniquet and loco-regional anaesthesia. We found that the pain scores during the anaesthetic administration and the surgical procedure were similar in two groups. Rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…The average range of motion of the wrist (flexion, extension, supination and pronation) recorded at three weeks, six weeks, three months and six months also showed a significant improvement similar to Dukan’s study that reported better wrist range of motion and QuickDASH scores and an earlier return to work [ 10 ]. In contrast, the clinical outcomes in Tahir et al’s study were not affected by the type of anesthesia [ 11 ].…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The average range of motion of the wrist (flexion, extension, supination and pronation) recorded at three weeks, six weeks, three months and six months also showed a significant improvement similar to Dukan’s study that reported better wrist range of motion and QuickDASH scores and an earlier return to work [ 10 ]. In contrast, the clinical outcomes in Tahir et al’s study were not affected by the type of anesthesia [ 11 ].…”
Section: Discussionsupporting
confidence: 77%
“…The average operative time was longer for the WALANT group (61.22 min) compared to the GA group (55.3 min) and the difference was statistically significant (p = 0.003). Previous studies by Dukan et al and Tahir et al found no difference in the operative time between WALANT and GA groups [ 10 , 11 ]. Both GA (n = 14) and WALANT (n = 11) groups had similar AO C2 type of radius fracture.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations